NUMERICAL INVESTIGATION ON THE FUSELAGE AIRFRAME OF LSU 05 NG AIRCRAFT - Hafid, M.; Nurrohmad, Abian; Ramadhan, Redha Akbar (BRIN Publishing, 2020)
In this paper, numerical investigation on the fuselage structure of LSU 05 NG was carried out. This fuselage is designed to carry the payload up to 30 kg. Statical numerical analysis using finite element method was done using Simulia Abaqus. The fuselage structure that has been design consists of frame, longeron, and skin that can also be semi-monocoque structure. This airframe use combination of balsa and GFRP type of composite as the material. There are three load case: take-off condition, cruise condition, and landing condition. Tsai-hill failure criteria is used to investigate the strength of the composite structure due to the load that applied. Maximum stress from this calculation is 48 Mpa at the ground condition (take-off and landing) while the cruise stress analysis is 16 Mpa. The maximum tsai-hill criterion is 0,83. With such simulation results it can be said that the fuselage structure is still safe when operated and can also be optimized for several components so that the weight of the aircraft can be reduced.